VSE 101 – Who, What, When, Where, Why, How. Issue 1 (July 2017) - Ptack, Ken
Abstract: International standards capture proven engineering practices for systems engineering and software engineering development. The perception by very small entities (VSEs) is that these standards are developed and targeted for use by large enterprises. However, governments and industry alike recognizes that VSEs, consisting of 25 staff members or less, constitute a majority of the systems and software developers throughout the world. During a world‐wide survey of many different domain VSEs, it was verified that existing ISO standards were "too complicated" for use by VSEs. In 2005, the first meeting of ISO/IEC JTC1 SC7 Working Group (WG) 24 was held. This ISO WG is mandated to develop standards and guides for VSE use, thus the work on the ISO/IEC 29110 series began. The paper will address how the ISO/IEC 29110 series and the INCOSE VSE WG deployment packages (DPs) work collaboratively to help VSEs incorporate systems engineering concepts within their entities. The use of these systems engineering concepts can provide VSEs the opportunity to successfully participate and grow in the global market environment.